A cross-cultural comparison of concepts in computer science education. Issue 4 (3rd August 2015) - Zendler, Andreas; McClung, O. William; Klaudt, Dieter
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The development of a K-12 computer science curriculum based on constructivist principles needs to be informed by knowledge of content and process concepts that are central to the discipline of computer science. The paper aims to discuss this issue. Design/methodology/approach – Taking a cross-cultural approach and using an experimental design (a SPF-215×16 split-plot design), this study compares the combinations of content and process concepts identified as important in Germany with those considered relevant in the US context. Findings – First, the combinations of content and process concepts identified in the German context can be generalized to the US context. Second, it is possible to identify combinations of content and process concepts in the US context that are also important in the German context. Third, content and process concepts identified in the two contexts can be integrated to generate a broader perspective that is valid for both contexts. Practical implications – The results can be used for consolidating available curricular drafts for computer science as a teaching subject at school of the type available in many. The present findings are of great relevance for research-based approaches to the pre- and in-service education of computer science teachers. The methodological approach taken is important in efforts to consolidate curricular models of computer science education, as have been initiated by the Bologna process in Europe and by the organizations Association for Computing Machinery, Association for Information Systems, and Institute of Electrical and Electronic Engineers-Computer Society in the USA. Originality/value – Results show that competence areas of central concepts identified in the two contexts can be integrated to generate a broader perspective that is valid for both contexts.